An Audit of the effect of Bone Morphogenetic Protein-2 Treatment in patients with non-union of long bone fractures - Janjua, Fateh Ali; Obada Hasan; Fatima Abbas Naqvi; Sarosh Madhani; Masood Umer (Journal of the Pakistan Medical Association, 2022)
Objective: To evaluate the outcomes, clinical and radiological application of Bone Morphogenetic Protein-2 alone versus Bone Morphogenetic Protein-2 with autograft in long bone non-unions. Methods: A prospective review of patients was done with fracture non-union admitted to Aga Khan University Hospital, Karachi, from January 2016 to January 2019. The patients were divided into two groups; those exposed to Bone Morphogenetic Protein-2 alone in group 1, and those exposed to Bone Morphogenetic Protein-2 plus autologous graft in group 2. Results: Background characteristics of both the groups were analysed. Patients were followed up at 6 and 12 weeks through their medical records. The primary outcome was postoperative union at 6 weeks or 12 weeks. Union was defined by having the clinical union as well as the radiological union at the same time of assessment. Of the 80 patients enrolled, 13(16.25%) were excluded, and 5(6.25%) were lost to follow-up. The final sample had 62(77.5%) patients; 35(56.5%) in group 1, and 27(43.5%) in group 2. Union at 6 weeks was observed in 13(21%) patients; 8(62%) in group 1, and 5(38%) in group 2. Union at 12 weeks was observed in 38(61%) patients; 20(53%) in group 1, and 18(47%) in group 2. Conclusion: Results showed that using the adjuvant treatment alone was not worse than using it along with bone autologous graft. Key Words: Fracture, Non-union, Trauma, Bone-graft.